Forward osmosis membrane bioreactor using Bacillus and membrane distillation hybrid system for treating dairy wastewater. Issue 12 (25th May 2021) - Song, Hongwei; Liu, Jinrong
ABSTRACT: Wastewater recycling is one of the best ways to alleviate water scarcity and water/wastewater pollution. The dairy industry is the largest industrial food wastewater source in many countries. In this study, we used a forward osmosis membrane bioreactor (FOMBR) and membrane distillation (MD) hybrid system to recycle dairy wastewater. And we developed a new Bacillus -FOMBR inoculated with salt-tolerant Bacillus sludge to protect against the negative effects of accumulated salt on sludge characteristics, microbial community and treatment effectiveness, and to alleviate membrane biofouling. A laboratory-scale FOMBR-MD experiment was operated for 40 days and water flux, salinity change, sludge characteristics, microbial community, nutrient removal efficiency, and FO membrane fouling were investigated. The Bacillus -FOMBR showed a small decrease in biomass concentration, and the hybrid system removed almost 100% of the contaminants. High-throughput sequencing analysis indicated that Pirellula and Hyphomicrobium species dominated the Bacillus- FOMBR, which are obliged to perform heterotrophic nitrification and aerobic denitrification. These nitrogen-removing bacteria ensured high nitrogen removal efficiency of the bioreactor. The total nitrogen (TN) concentration in the bioreactor increased and then decreased, which did not continuously increase as occurred in conventional FOMBRs. The TN removal efficiency of the bioreactor was mostly above 40% and the highest reached 79%. Besides, the Bacillus- FOMBR suffered little membrane biofouling because of the quorum quenching effect of the Bacillus species. We speculate that the Bacillus -FOMBR has potential to treat high-salt wastewater and high strength ammonia-nitrogen wastewater. GRAPHICAL ABSTRACT: The laboratory-scale FOMBR-MD hybrid system (FS = feed solution, FO = forward osmosis, DS = draw solution, AGMD = air gap membrane distillation).